Paralympic brain - compensation and reorganization in human brain - Nakazawa, K. (Japanese Journal of Physical Fitness and Sports Medicine, 2020)
One of the primary goals of basic neurorehabilitation studies is to figure out the underlying neural mechanisms in the re-organization of central nervous system after rehabilitation interventions. From this perspective the athletes with disabilities, such as Paralympic athletes would be the attractive research model, since they can show the use-dependent plastic changes in CNS after the long-term intervention of intensive physical training. We have recently found that the brains of Paralympic athletes are reorganized uniquely in such a manner dependent on disability types and athletic-specific training. Factors playing the major roles in the reorganization are most probably use-dependent plasticity and disability-specific compensations. In this presentation our current data obtained from the following Paralympic athletes with various types of disabilities who have been engaged in different sports will be introduced. A) A long jumper and a high jumper with below knee amputee Both para-athletes showed bilateral activation of the leg motor area when they were producing knee joint torque during fMRI recording, while no such bilateral motor area activation was observed for the non-amputated leg. The transcranial magnetic stimulation (TMS) study for the high jumper confirmed that the ipsilateral corticiospinal tract of the amputated side knee ex-tensor has the higher excitability and is recruited when he produces knee extension torque to move the prosthesis. B) The archer with congenital upper-limb loss The highly skilled lower leg function and large expansion of toe motor area in the primary motor cortex were observed with both fMRI and TMS experiments. C) Power lifters with spinal cord injury The specifically improved upper-limb motor function assessed with the isometric grip force stability test after spinal cord injuries was found. The subsequent experiment showed that the higher stability in grip force was common in persons with complete spinal cord injury regardless of sports participation, although there is still possibility that the higher force stability would be further improved in power lifters. D) A swimmer with cerebral palsy Electromyographic (EMG) activity and motion recording were performed during swimming for the former Paralympic gold medalist. The EMG activities and motion analysis showed that she performed well-coordinated dynamic swimming movement without spasticity in water, whereas on land she showed a typical hemiplegic type of posture and gait pattern with spastic elbow flexor activity. Although the MRI image of her brain revealed a large lesion in her left sensory-motor area, the remarkable brain reorganization was found to occur with the TMS experiment. The neural mechanisms enabling dynamic swim motion in water will be presented with the current knowledge regarding interaction between autonomic nervous activity and motor system, which can be applied to neurorehabilitation for patients after damages to the CNS such as stroke and spinal cord injury.